Comorbidities and their link with individual health status: A cross-sectional analysis of 23, 892 people with knee and hip osteoarthritis from primary care. (8th May 2020) - Muckelt, Paul Edward; Roos, EM; Stokes, M; McDonough, S; Grønne, DT; Ewings, S; Skou, ST
Objectives: Robust data on the impact of comorbidities on health in people with osteoarthritis (OA) are lacking, despite its potential importance for patient management. Objectives were to determine coexisting conditions in people with OA in primary care and whether more comorbidities were linked with individual health status. Methods: A retrospective analysis of 23, 892 patients with knee and hip OA was conducted to determine comorbidities present (number/clusters) and how these linked with pain intensity (0–100), widespread pain (site numbers), medication usage (paracetamol, nonsteroidal anti-inflammatory drugs, opioids), quality of life EuroQol five dimension scale (EQ-5D), and physical function (walking speed) using independent t -tests or χ 2 test. Results: Sixty-two percent of people with OA treated in primary care had at least one comorbidity; hypertension (37%), heart disease (8%), and diabetes (7%) being most common. Outcome measures worsened with more comorbidities (0–4+ comorbidities); pain intensity [mean (SD)] 46(22)–57(21); number of painful sites 3.7(3.0)–6.3(5.4); quality of life 0.73(0.10)–0.63(0.15); walking speed 1.57 m/s (0.33)–1.24 m/s (0.31), while the proportion of people using pain medication increased from 0 to 2 comorbidities (58–69%; p < 0.001), with an increase in opioid use from 4.6% to 19.5% with more comorbidities (0–4+ comorbidities). Conclusion: Most people with knee or hip OA in primary care have at least one other long-term condition. A greater number of comorbidities is linked with worsening health, highlighting the importance of screening for comorbidities when treating patients with OA. It is important for clinicians to consider how OA treatments will interact and affect other common comorbidities.